Implementation of the Independent Curriculum in Islamic Education (PAI) Subjects at SMP Negeri 1 Buay Bahuga - Nur Muhammad Gasmi; Subhi Nur Ishaki; Eti Hadiati; Sovia Mas Ayu; Ahmad Fauzan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this research is to understand the teachers' comprehension and challenges regarding the implementation of the Merdeka Curriculum in the subject of Islamic Education (PAI), as well as the strengths and weaknesses in its implementation at SMP Negeri 1 Buay Bahuga. This study uses qualitative field research, with primary data sources being individuals (informants), and the research findings are summarized in statements consisting of sentences and words. The researcher conducted direct observations to gather necessary information for the study. Research findings show that the Merdeka curriculum has significant potential to improve the quality of education at SMPN 1 Buay Bahuga, particularly in the subject of Islamic Education (PAI). However, its successful implementation is heavily dependent on the readiness and capability of teachers, as well as continuous support and training.